Double stigma in mental health: epilepsy and mental illness. Issue 4 (July 2020) - Mula, Marco; Kaufman, Kenneth R.
Abstract : Background: Epilepsy and mental illness share similar problems in terms of stigma, as a result of centuries of superstition, ignorance and misbeliefs. Stigma leads not only to discrimination and civil and human rights violations but also to poor access to healthcare and non-adherence or decreased adherence to treatment, ultimately increasing morbidity and mortality. Despite continuous efforts in fighting stigma in these conditions, there is very limited knowledge on the phenomenon of double stigma, meaning the impact of having two stigmatised conditions at the same time. Aims: To discuss double stigma in mental health with special reference to epilepsy. Method: Articles were identified through searches in PubMed up to 31 October 2019 using the search terms 'epilepsy', 'psychiatric disorders', 'stigma' and additional material was identified from the authors' own files and from chosen bibliographies. Results: Double stigma is gaining attention for other stigmatised medical conditions, such as HIV, however, the literature on epilepsy is almost non-existent and this is quite astonishing given that one in three people with epilepsy have a lifetime diagnosis of a psychiatric condition. Felt (perceived) stigma and psychiatric disorders, particularly depression, create a vicious circle in epilepsy maintaining both, as depression correlates with stigma and vice versa as well as epilepsy and depression serving as bidirectional risk factors. This phenomenon has no geographical and economic boundaries as similar data have been reported for low-income and high-income countries. Conclusions: Governments and policymakers as well as health services, patients' organisations, families and the general public need to be aware of the phenomenon of double stigma in order to develop campaigns and interventions tailored for these patients.